Exploring Employee Turnover Intention: PT. Esta Dana Ventura Case - Syamrul, Syamrul; Modding, Basri; Serang, Serlin; Arifin, Zaenal (Universitas Negeri Gorontalo, 2024)
Purpose: The purpose of this study to determine the effect of workload, work stress and burnout on turnover intention employee of PT. Esta Dana Ventura Branch of Makasar.Design/Methodology/Approarch: This research uses explanative research with a quantitative approach. A sample of 120 respondents was selected for data collection using simple random sampling method. A closed questionnaire was used which was facilitated through Google Forms. The collected data was analyzed using a Likert scale model and t test.Findings: This study confirms a positive and significant relationship between workload, work stress, and burnout with employee turnover intention. These results support theories that describe excessive workload, high stress levels, and levels of burnout with the desire of employees to leave the organization. These implications can enrich our understanding of how these variables are interrelated and how they impact employee attitudes and behavior. Based on the research results, PT. Esta Dana Ventura Makassar Branch should take some practical steps Encouraging open communication between management and employees is very important. This can help identify problems related to workload, work stress, and burnout that affect employees. Management needs to open effective communication channels to provide opportunities for employees to convey problems and problems that are experienced.